Environmental Carrying Capacity as a Solution to Overlapping Forest Area Permits in Bulungan District, North Kalimantan - Tjahjo Tri Hartono; Iksal Yanuarsyah; Yudi Setiawan; Fikri Sakti; Endah Nadiya Stephanie (Jurnal Rekayasa Lingkungan dan Biosistem, 2023)
Research on the carrying capacity of the environment for mining activities, as indicated by the dynamics of stored carbon stocks will be carried out in Bulungan Regency, North Kalimantan in early 2022. Data was collected both through literature studies and surveys calculating tree diameter at breast height in the field as a basis calculation of stored carbon stock. Land cover spatial data analysis is used as a reference for calculating stored carbon stocks at the study site. The results of a comparison of stored carbon stocks between forest and land clearing and reclamation based on planned mining activities show that the area that can be utilized is 1,578.3 Ha. There are efforts to restore carrying capacity and carrying capacity based on mining activities with broad impacts that can be used is 1,947.84 Ha. The usable area can be increased 1.2 times from the recommended area (2,337,415 Ha) to accommodate the required land as an overburden area. This addition is made possible through the application of various appropriate technologies. The carrying capacity of the environment in this study, although only limited to the dynamics of stored carbon stocks, shows that the results can be used as a solution for overlapping permits in forest areas in accordance with the laws and regulations in effect since the Ministry of Environment and Forestry has so far provided a maximum area of 10 percent of the area areas affected by overlapping cases.